Physical Characteristics of von Willebrand Factor Binding with Platelet Glycoprotein Ibɑ Mutants at Residue 233 Causing Various Biological Functions - Masamitsu Nakayama; Shinichi Goto; Shinya Goto (TH Open, 2022)
Glycoprotein (GP: HIS1-PRO265) Ibɑ is a receptor protein expressed on the surface of the platelet. Its N-terminus domain binds with the A1 domain (ASP1269-PRO1472) of its ligand protein von Willebrand factor (VWF) and plays a unique role in platelet adhesion under blood flow conditions. Single amino acid substitutions at residue 233 from glycine (G) to alanine (A), aspartic acid (D), or valine (V) are known to cause biochemically distinct functional alterations known as equal, loss, and gain of function, respectively. However, the underlying physical characteristics of VWF binding with GPIbɑ in wild-type and the three mutants exerting different biological functions are unclear. Here, we aimed to test the hypothesis: biological characteristics of macromolecules are influenced by small changes in physical parameters. The position coordinates and velocity vectors of all atoms and water molecules constructing the wild-type and the three mutants of GPIbɑ (G233A, G233D, and G233V) bound with VWF were calculated every 2 × 10−15 seconds using the CHARMM (Chemistry at Harvard Macromolecular Mechanics) force field for 9 × 10−10 seconds. Six salt bridges were detected for longer than 50% of the calculation period for the wild-type model generating noncovalent binding energy of −1096 ± 137.6 kcal/mol. In contrast, only four pairs of salt bridges were observed in G233D mutant with noncovalent binding energy of −865 ± 139 kcal/mol. For G233A and G233V, there were six and five pairs of salt bridges generating −929.8 ± 88.5 and −989.9 ± 94.0 kcal/mol of noncovalent binding energy, respectively. Our molecular dynamic simulation showing a lower probability of salt bridge formation with less noncovalent binding energy in VWF binding with the biologically loss of function G233D mutant of GPIbɑ as compared with wild-type, equal function, and gain of function mutant suggests that biological functions of macromolecules such as GPIbɑ are influenced by their small changes in physical characteristics.